Developing ASKIT Digital Board Game as The Learning Media to Teach English On Asking And Giving Information Materials using ADDIE - apriliyah, Dwi estiana; Christanti , Ana (Journal of English Teaching, Literature, and Applied Linguistics, 2025)
This study aims to develop a digital board game called ASKIT (Amazing Snakes Knowledge and Information Trail) as a learning media to teach English, particularly the topic of asking and giving information for 8th-grade students at SMP Al-Manshur. The research employed the ADDIE model, consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. In the development process, Canva and Genially were used to design the game and integrate interactive materials, quizzes, and audio elements. Validation was conducted by media and material experts, showing high feasibility scores—95% from the media expert and 92.5% from the material expert. The implementation phase involved 21 students and demonstrated increased motivation, engagement, and speaking skills, confirmed by teacher and student questionnaires. The findings indicate that ASKIT is effective in making the learning process more interactive and enjoyable. It also helps address the lack of student interest due to monotonous teaching methods. The study concludes that digital board games can be a practical and innovative solution in English language education. However, the research was limited to a single school with a small number of participants and did not conduct long-term testing to evaluate retention or continuous impact. Future studies should involve broader implementation and extended evaluation periods.